Biological Control of Agriculture Insect Pests - Holmes, Leonard; Mandjiny, Sivanadane; Upadhyay, Devang (European Scientific Journal, ESJ, 2016)
This review summarizes the efficacy, advantages and safety of using biological agents to suppress and control damage done to crops by insects. Biocontrol has been generally shown to be safe to plants, animals, humans and the environment. This is in stark contrast to more widely used chemical insecticides that often results in environmental pollution causing harm to humans and the environment. Biocontrol manufacturers continue to develop new protocols for assessing agent safety, deploying and measuring treatment success. Government and manufacturing organizations are developing regulations to assure the safe and appropriate use of biocontrol. The benefits of biological control systems drive the increasing adoption of the technology. Protection of biodiversity and high benefit to cost ratio are obvious reasons to promote the use of biocontrol platforms. It will require education and awareness of the general public and those involved in agriculture to accept these alternative farming practices.